Perancangan Aplikasi Seluler Dokumentasi dan Informasi Hukum BPH Migas Berbasis Android - Yehezkiel Dicky Pandu Ferdinand1; Tjiong, Edwin (KALBISCIENTIA Jurnal Sains dan Teknologi, 2024)
This work presents the development of mobile application in Android OS to display legal documentation which are published by BPH Migas. The purpose of this work is to streamline the access to legal documents produced by BPH Migas by mobile device users. The development work was designed using agile framework and the application was implemented using Kotlin programming language. The result is a mobile application that can view, download, and share legal documents owned by BPH Migas